2021
DOI: 10.1155/2021/1405045
|View full text |Cite
|
Sign up to set email alerts
|

STAT1-Induced Upregulation lncRNA LINC00958 Accelerates the Epithelial Ovarian Cancer Tumorigenesis by Regulating Wnt/β-Catenin Signaling

Abstract: Background. Growing studies have demonstrated that long noncoding RNAs (lncRNAs) play important roles in tumor progression. In this study, we aimed to explore the potential roles of lncRNA LINC00958 (LINC00958) and its biological functions in epithelial ovarian cancer (EOC). Methods. The expression of LINC00958 in 11 cases of EOC and adjacent nontumor specimens and five cell lines was detected by qRT-PCR. CCK-8, colony formation, and flow cytometry assays were conducted to study the cell viabilities of EOC cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 31 publications
1
6
0
Order By: Relevance
“…Yuan et al (61) demonstrated that STAT1 could be recruited into the promoter of β-catenin to activate its expression, and this effect was regulated by IFN-γ. In epithelial ovarian cancer, STAT1 could promote the upregulation of long non-coding RNA LINC00958, thus accelerating tumorigenesis by modulating Wnt/β-catenin signaling (62). A similar cross-link of STAT1 and Wnt/β-catenin signaling was also observed in the present study.…”
Section: Discussionsupporting
confidence: 87%
“…Yuan et al (61) demonstrated that STAT1 could be recruited into the promoter of β-catenin to activate its expression, and this effect was regulated by IFN-γ. In epithelial ovarian cancer, STAT1 could promote the upregulation of long non-coding RNA LINC00958, thus accelerating tumorigenesis by modulating Wnt/β-catenin signaling (62). A similar cross-link of STAT1 and Wnt/β-catenin signaling was also observed in the present study.…”
Section: Discussionsupporting
confidence: 87%
“…1A ). Although carcinogenic functions have been previously identified in cervical cancer ( 38 ) and ovarian cancer ( 39 ), the role of BLACAT2 in UCEC remains unclear. BLACAT2 expression was therefore detected in clinical samples using RT-qPCR.…”
Section: Resultsmentioning
confidence: 99%
“…ISG20 promoted tumor progression in ccRCC and acted as a potential biomarker 16 . STAT1-induced upregulation lncRNA LINC00958 and promoted the tumorigenesis of OC via Wnt/β-Catenin signaling 17 . PSMA5 accelerated the tumorigenic process and involved in bortezomib resistance in prostate cancer 18 .…”
Section: Discussionmentioning
confidence: 99%